Amplified Fragment Length Polymorphism Diversity of Cultivated White Oyster Mushroom Pleurotus ostreatus - Muhammad Jusuf (Bogor Agricultural University, Indonesia, 2010)
Amplified fragment length Polymorphism (AFLP) analysis was performed to study the genetic diversity of fifteen isolates of white oyster mushroom (Pleurotus ostreatus) originated from different places in Indonesia (Java, Sumatra, Bali, and Kalimantan) and Thailand. The majority of studied isolates originated from commercial mushroom, and some of them were collected from nature. AFLP analysis revealed 202 loci of positive DNA bands. Heterozygosity value showed polymorphisms of the fifteen studied isolates. Correlation and cluster analyses of the isolates showed that isolate from Thailand (BNK isolate), isolate from Bogor (AMD isolate), and isolate from Purwokerto (USX isolate) were distinctly different from the other isolates indicated by positive bands with DNA size greater than 650 bp. Isolate from Kalimantan (BJM isolate) was distinctly different from Java island isolates. Generally there was no correlation of AFLP variability and geographic distribution of commercial strain isolates.